2012
DOI: 10.1016/j.jacc.2011.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification in Brugada Syndrome

Abstract: Our data show that VT/VF inducibility is unable to identify high-risk patients, whereas the presence of a spontaneous type I ECG, history of syncope, ventricular effective refractory period <200 ms, and QRS fragmentation seem useful to identify candidates for prophylactic implantable cardioverter defibrillator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
214
3
17

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(238 citation statements)
references
References 31 publications
4
214
3
17
Order By: Relevance
“…Recent evidence, however, has clearly demonstrated that family history has not been a reliable marker for high risk in patients affected by BrS 2. Moreover, the value of a family history of sudden death in BrS patients has been extensively investigated, and results in that family history of SCA are not predictive for future arrhythmic events 25, 26. Consistent with these studies, present results have also shown that family history of SCA was not associated with recurrent ICD shocks in Thai symptomatic BrS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence, however, has clearly demonstrated that family history has not been a reliable marker for high risk in patients affected by BrS 2. Moreover, the value of a family history of sudden death in BrS patients has been extensively investigated, and results in that family history of SCA are not predictive for future arrhythmic events 25, 26. Consistent with these studies, present results have also shown that family history of SCA was not associated with recurrent ICD shocks in Thai symptomatic BrS.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a male patient with Brugada syndrome and CAS alone developed sudden death because of recurrent VF without a cautionary chest pain or preceding ischemic ECG changes, although he was treated with antianginal agents, including CCBs ( Figure 5). Because the role of electrophysiological testing for predicting OHCA remains controversial in Brugada syndrome, 19 dual induction tests might be less reliable in patients with the disorder.…”
Section: Long-term Prognosis According To the Presence Or Absence Of mentioning
confidence: 99%
“…42 Although large studies agree that electrophysiological study inducibility is greatest among BrS patients, there has been no consensus on the value of the EP study in predicting outcome. 6,43,44 Several consensus documents have addressed this issue and the current recommendation is to implant an ICD in inducible patients (Class IIb indication). …”
Section: -40mentioning
confidence: 99%